Hubungan Faktor Penyebab Tingkat Kelelahan pada Pekerja Tambang Pengolahan Mineral Tembaga dan Emas - Khaerani Lestari; Aditya Fadila Muhamad; Arif Susanto; Edi Karyono Putro; Fanny Sarah Yuliasari (Jurnal Kesehatan Komunitas, 2020)
Fatigue has a significant impact on the economy of a region. This is because it leads to absenteeism, decreased productivity, health costs, and accidents. It is something complex primarily caused by 2 factors, including work and non-work fatigue. The purpose of this study therefore is to determine the factors associated with the fatigue level in copper and gold ore processing workers. It uses a cross-sectional design with the Industrial Fatigue Research Committee (IFRC) questionnaire to measure the fatigue level and The Pittsburgh Sleep Quality Index (PSQI) of 260 respondents working in the copper and gold ore processing firm. The results showed that 1 worker (0.4%) experienced severe fatigue, and 12 workers (4.6%) moderate, 243 (93.5%) mild fatigue, while only 4 (1.5%) were not affected. Additionally, there is a significant relationship between fatigue levels with sleep quality. In conclusion, poor sleep has the potential to increase fatigue. Companies therefore need to provide training related to the management of fatigue and sleep quality for workers.